Penerapan Model Pembelajaran Berbasis Masalah untuk Meningkatkan Hasil Belajar IPA Siswa Kelas VIII SMPN 1 Selong pada Masa Pandemi Covid Tahun Pelajaran 2021/2022 - Juhairiah (LAMBDA : Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2021)
The type of research conducted is Class Action Research that is carried out in the form of an action cycle. The purpose of this class action research (PTK) is to find out the extent of enhancing student learning outcomes on IPA lessons by applying a Problem-Based Learning Model. In this class action research (PTK) conducted in 2 cycles, from the results of actions carried out proven to improve student learning outcomes by achieving a set classical completion of 85%. Classical completion of 67% is obtained in cycle I, can increase in cycle II to 95%. In terms of student activity there is also an increase that in cycle I obtained active category increases to a very active category. The results of this action study show that the application of problem-based learning models can improve student learning outcomes on IPA lessons with completion of up to 95%.